Wacana Terkait Civil Phobia Dalam Video Youtube Berjudul Presiden Prabowo Menjawab: Analisis Wacana Digital Rodney H.Jones - Nanda Mirrotul Waliidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
An exclusive interview titled “President Prabowo Answering” involving seven national media journalists discussed political and social issues as a form of the President's accountability to the public as well as an effort to improve political communication. This research aims to reveal the civilphobia discourse through Rodney H. Jones' digital discourse analysis, focusing on four elements: text, context, action and interaction, as well as ideology and power. The results of the analysis show that in the text element, there is a statement from the President that seems to reject criticism and blame the third party. In the context, it is known that the invited journalists came from credible media, and the video was made in response to public unrest. The action and interaction elements were analyzed through responses on social media such as YouTube, TikTok, X (Twitter), and Instagram, which showed active discussions about the term civilphobia. Meanwhile, in the aspect of ideology and power, it was found that YouTube is an effective medium in spreading ideology and shaping public perception. This video reflects how digital media plays a strategic role in building political communication between the government and the public, as well as in shaping massive public images and opinions.